Towards a common approach for managing food allergy and serious allergic reactions (anaphylaxis) at school. GA2LEN and EFA consensus statement - Antoine Deschildre; Montserrat Alvaro‐Lozano; Antonella Muraro; Marcia Podesta; Debra deSilva; Mattia Giovannini; Simona Barni; Timothy E. Dribin; Mónica Sandoval‐Ruballos; Aikaterini Anagnostou; Alessandro Fiocchi; Alice Toniolo; et al. (Clinical and Translational Allergy)
Abstract GA2LEN and EFA propose minimum specifications for all industrialised countries/regions to work towards to support students with food allergies in educational settings. We reviewed research and legislation and gained feedback from over 100 patient and professional groups. We built shared expectations around: 1. training all school staff about what food allergy is, the symptoms of allergic reactions, what to do in an emergency, and when and how to use and store devices that laypeople can use to administer adrenaline (epinephrine). 2. preventing allergic reactions by using clear labelling on school menus and prepacked and non‐prepacked foods and regular cleaning where students eat. 3. preparing for serious allergic reactions, with written emergency action plans for every student with food allergies, legislation allowing schools to store adrenaline for anyone who needs it in an emergency (not just those prescribed it), and training and legal safeguards for staff administering adrenaline. 4. including affected students by discussing food allergy in the curriculum, raising awareness among all students and caregivers and reviewing school processes regularly. It is time for national and international action at the policy level. Patient groups, education networks and professional societies all play a role in campaigning for shared next steps.